ASSESSING THE VIEW OF CRIMINOLOGY SCIENCE IN SENIORITY VIOLENCE CASES - Desideria Desideria; Harkirtan Kaur; Winnie (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Seniority is one of the acts that often occurs in Indonesia, which until now can still be seen clearly in the world of Indonesian education system. Seniority is also a polemic which is quite difficult to find a solution to. The case of seniority itself occurs from the junior high school, high school level, to the lecture level. The types of seniority violence also vary, from verbal abuse to physical violence. The consequences arising from the act of seniority also vary, from physical injury to trauma, even to death. At the junior and senior high school levels, cases of seniority violence often appear during the Student orientation period. The school holds an orientation period at the beginning of the school year with the aim of showing students about the world of education and the new school atmosphere, so that students are expected to adapt to their new environment. But unfortunately, sometimes activities whose initial purpose is to make students adapt and recognize their new environment, it often causes havoc for new students. In July 2019, the Basic Activity of Physical and Mental Coaching (Madabintal) held by the semi-military school for Indonesian Cadets in Palembang as part of the MPLS activities resulted in 2 fatalities due to seniority violence. The existence of a culture of seniority on the grounds of mentally training students cannot be justified, because the violence of seniority can actually damage a person's mentality and make him lack self-confidence.